Removal of SOST or blocking its product sclerostin rescues defects in the periodontitis mouse model. Issue 7 (10th March 2015) - Ren, Yinshi; Han, Xianglong; Ho, Sunita P.; Harris, Stephen E.; Cao, Zhengguo; Economides, Aris N.; Qin, Chunlin; Ke, Huazhu; Liu, Min; Feng, Jian Q.
ABSTRACT: Understanding periodontal ligament (PDL) biology and developing an effective treatment for bone and PDL damage due to periodontitis have been longstanding aims in dental medicine. Here, we first demonstrated by cell lineage tracing and mineral double‐labeling approaches that murine PDL progenitor cells display a 2‐ and 3‐fold higher mineral deposition rate than the periosteum and endosteum at the age of 4 weeks, respectively. We next proved that the pathologic changes in osteocytes (Ocys; changes from a spindle shape to round shape with a >50% reduction in the dendrite number/length, and an increase in SOST) are the key pathologic factors responsible for bone and PDL damage in periostin‐null mice (a periodontitis animal model) using a newly developed 3‐dimensional FITC‐Imaris technique. Importantly, we proved that deleting the Sost gene (a potent inhibitor of WNT signaling) or blocking sclerostin function by using the mAb in this periodontitis model significantly restores bone and PDL defects ( n = 4‐5; P < 0.05). Together, identification of the key contribution of the PDL in normal alveolar bone formation, the pathologic changes of the Ocys in periodontitis bone loss, and the novel link between sclerostin and Wnt signaling in the PDL will aid future drug development in the treatment of patients with periodontitis.—Ren, Y., Han, X., Ho, S. P., Harris, S. E., Cao, Z., Economides, A. N., Qin, C., Ke, H., Liu, M., Feng, J. Q. Removal of SOST or blocking its product sclerostin rescues defects in the periodontitis mouse model. FASEB J . 29, 2702‐2711 (2015). www.fasebj.org